Analyzing Materials Using Joint X-Ray Fluorescence and Diffraction Spectra - Mikhailov, Igor F. (Cambridge Scholars Publisher, 2020)
This book presents a complex approach to material composition determination based on the analysis of the joint X-ray spectrum, including fluorescence, scattering, and diffraction reflections. It considers fluorescence, scattered, and diffracted radiations within the common problem of analytical spectrum formation. The complex methods for analyzing the material composition by joint spectra of fluorescence, Compton scattering and diffraction proposed here allow for a widening of the area of the application of X-ray methods.The book will be useful for specialists in the field of solid state physi.